Review and Evaluation of Root Respiration and of Natural and Agricultural Processes of Soil Aeration - Ben-Noah, I. (2020)
Soil respiration rate is also affected by climatic conditions, where a temperature difference of 10°C increases O2 consumption (and CO2 production) two‐ to threefold. The ratio between emitted CO2 and inspired O2 (respiratory quotient) is not unity (on a molar basis) but rather depends on the types of respiring populations and environmental conditions. Reduced O2 and elevated CO2 concentrations negatively affect plant growth and productivity. These conditions are correlated mostly with wet and warm soils, such as intensively irrigated fields with fine‐textured soils (high water retention) during the summer. Oxygen‐availability quantifiers such as O2 concentration, air content, and O2 diffusion rate are superior to other quantifiers such as soil properties (e.g., soil texture, porosity) and redox potential. In the last few decades, several active aeration methods have been proposed and evaluated, such as adding air or O2 bubbles or H2O2 to the irrigation water and air injection into the soil. Although these methods have given mainly positive results, none is widely used in agricultural practice, due mainly to a lack of profitability potential, field‐scale proof demonstration, and a coherent protocol for field application.